Central retinal artery occlusion (CRAO) - case report - Tkaczyk, Jędrzej; Brożyna, Klaudia; Baltaziak, Katarzyna; Ciechański, Krystian; Nowakowska, Dominika; Rejdak, Robert (Journal of Education, Health and Sport, 2018)
Central retinal artery occlusion (CRAO) is an ophthalmic emergency, most commonly caused by an embolism, usually from the carotid arteries. It can be considered as an acute stroke of the eye, and is an ocular analogue of cerebral stroke. The incidence of CRAO is estimated to be 1 in 100 000 people. Risk factors include hypertension, carotid atherosclerosis, structural cardiac pathology, coronary heart disease, cerebral vascular accident, and diabetes mellitus. CRAO usually presents with a sudden, painless loss of vision. 52 - year old male was admitted to the Ophthalmology ER, reporting a painless monocular vision loss in a right eye for two days. After such a long time from the occurrence of symptoms, there weren’t any possible treatment methods for this patient, besides preventing future embolic events. Ophthalmological examination showed only a light perception in a right eye and vision in the left eye was 1.0. Patient was diagnosed to identify risk factors of CRAO: hypertension, hypercholesterolemia, atherosclerosis or thrombophilia. He was qualified for a careful observation for the atherosclerotic risk factors and educated, that in case of occurrence of the similar symptoms, he needs to report to a Ophthalmologist immediately. Currently, there are two main types of treating an acute non-arteritic CRAO: the first: ‘standard’, non-invasive method, and the second: using the thrombolytics deployed intravenously or intra-arterially. Unfortunately, they couldn’t be used to treat described patient, since he has already been in a late phase of CRAO.